How do vigilance and feeding by common cranes Grus grus depend on age, habitat, and flock size? - Avilés, Jesus M.; Bednekoff, Peter a (Journal of Avian Biology, 2007)
Animals often spend less time vigilant and more time feeding when foraging in larger groups. This group-size effect does not, however, consider if larger groups differ systematically from smaller ones: Large groups could form in different habitats than small groups or be composed of a different mix of ages or classes than small groups. We examined how habitat differences and flock size and composition explain feeding and vigilance rates in common cranes Grus grus, wintering in holm oak Quercus ilex dehesas of Spain. Flock size and composition were related to habitat type in cranes: flocks formed in areas sown with cereal crops were larger than flocks formed in set aside areas. Vigilance rate depended on habitat but decreased with increasing flock size in a similar way across all habitats. Juveniles were less vigilant than adults and showed little change in vigilance with flock size. Vigilance increased and feeding time decreased over months from November through February. Our results show that vigilance is affected by habitat but that the group size effect on vigilance is not the product of differences between habitats in group size or composition.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: Cranes; Dehesa; feeding; flock size; holm oak canopy (voyant); vigilance